Adaptive micro electret vibrational energy harvester - Tao, Kai (Nanyang Technological University, 2016)
Recent advances in embedded autonomous wireless sensors and low-power electronic devices have led to the rapid emergence of micro-scale energy harvesting technologies. Such harvesters may pave the primary step forward to actualizing of self-autonomous devices and performing of intelligent monitoring activities. Most resonant-based energy harvesters are currently only efficient in a narrow bandwidth near the sole resonance and could only perform optimally when their oscillation is precisely aligned with the single designed excitation direction. Such characteristics would limit their applications in the real-world environment where a wide spectrum with frequency-variant or direction-random vibrations usually exists. This thesis investigates adaptive methods to extend frequency spectrum bandwidth and multi-directional response of the harvester from both sophisticated electromechanical coupling of electrostatic energy harvesting systems and advanced mechanical configuration perspectives. Electret-based electrostatic vibration energy harvesters (e-VEHs) are explored in this work as they are advantageous in terms of silicon CMOS compatible processes, low operating frequencies as well as great flexibilities via the capability to design the mechanical and electrical features separately. To make the energy harvester adaptive to multiple excitation directions, two-dimensional (2D) dynamic response of a symmetrical spring-mass resonant system was investigated by combining its two primary orthogonal oscillation modes. The energy harvesting efficiency of the proposed 2D resonators were theoretically calculated to be superior to conventional 1D counterpart. A rotational symmetrical circular resonator composing of a movable disk-shaped seismic mass and suspended by three sets of spiral springs had been successfully designed, fabricated and characterized. A general numerical model based on the experiment results was created to describe the dynamic motion of the seismic mass, which would form a basis in developing a real 2D energy harvester. Prototype with sandwich structure was studied that had two separate capacitive circuits 180° out-of-phase with each other to be integrated into a single seismic mass system. This configuration had its merits in that both the vertical pull-in electrostatic force as well as the horizontal damping force could be reduced. With the present prototype, an overall output power of 0.12 µW was obtained for the two capacitive parts at an acceleration of 0.2g at 125 Hz. To cater to the broadband spectrum exhibited by ambient vibrations, two approaches were intensively investigated that sought to expand frequency spectrum of energy harvesters, namely ‘nonlinear technique’ and ‘multi-frequency energy harvesting’. Nonlinear technique was considered to be an effective way to enlarge the frequency spectrum by utilizing spring softening and hardening effects. Although numerous methods had been proposed to induce nonlinearities of energy harvesting system previously, electrostatic nonlinearity introduced by electret surface potential, as an inherent feature of e-EVHs, was seldom studied up to date. It was practically more advantageous and readily compatible with Micro-Electro-Mechanical-System (MEMS) energy harvesting devices. To study the spring softening nonlinear phenomenon of electret-based energy harvesting system, an analytical nonlinear model of e-VEH was derived, where the electromechanical coupling effect arising from mechanical and electrical domains was incorporated. As a proof of concept, an out-of-plane energy harvester device with dual-charged electret plates has also been designed and fabricated. At a high excitation level of 0.48 g, the experimental results showed that the 3-dB bandwidth was enlarged by 2.85 times from 1.3 Hz (bandwidth of linear response) to 3.7 Hz. An optimal output power of 0.95 µW was also achieved with a low resonance of 95 Hz. Compared with other broadband approaches involving extra mechanical components and tuning efforts, multi-frequency technique exploiting multiple vibration modes of single two-degree-of-freedom (2DOF) system provides a simple and reliable solution to increase the energy harvesting effectiveness. By precisely tuning the accessory mass, the first two resonances of primary mass can be tuned close to each other while maintaining comparable magnitudes. This enables both modes to contribute towards the overall energy harvesting. A lumped parametric model of 2DOF vibrational system was built and examined for its energy harvesting capabilities. Electret-based MEMS devices are particularly suited to such multi-frequency technique, where various parameters, such as beam width and seismic mass, can be precisely controlled through lithography process. Thereby, a 2DOF e-VEH was designed and implemented as proof of concept. The experimental results were in good agreement with the numerical models and Finite Element Analysis (FEA). With further increased excitation accelerations, the 2DOF e-VEH system demonstrated a spring hardening nonlinear effect, where the first peak was capable of being driven towards convergence with the second one to achieve a broadband energy harvesting system. Such novel nonlinear two-degree-of-freedom (2DOF) energy harvesting system combines advantages of both multi-modal energy harvesting and the nonlinear technique, which offers new insight of increasing bandwidth with hybrid broadband mechanisms.